Considerações sobre a metafilsofia de Richard Rorty - Brittes, Vinícius dos Santos (2015)
The present work is dedicated to a contemporary author who emphasized the incessant movement of the human species in their search for meaning: Richard Rorty. In this age-old effort to create meanings, thought manifested itself in many ways and in many different styles, and these changes have shaped the reason through time. The philosophy of Rorty is a "disenchantment" of philosophy, because undermines traditional concepts employed in philosophical inquiry and ultimately radically change the very notion of philosophy and what is philosophize. Thus, the insistent search for a last ground of knowledge, the attempt of philosophers - and scientists - to unveil the reality in their nature, are placed in check by Rorty, in favor of a much more "modest" purpose: achieve the best possible way to deal with the world without unequivocal or absolute assumptions. The development of these critical first appears in the book Philosophy and the Mirror of Nature, published in 1979, a work of great impact in contemporary philosophy that put Rorty as one of the exponents of current neopragmatist. Rorty stands out in contemporary philosophy to be an essentially combative author. His writings pursue a very clear proposal: to overcome some traditional ideas that dictate the philosophical agenda at least since Plato. As a representative of pragmatism, Rorty's effort is to show the futility of certain ideas and (pseudo)problems that generate for thought and research. The result of this effort reveals a complete transformation of philosophy and, beyond this, much of the western culture. This work aims to present and evaluate some of the main theses of Rorty.